2022
DOI: 10.1088/1361-6587/ac4856
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of charge exchange on beam ions in MAST-U

Abstract: A model for simulating charge exchange (CX) of fast ions with background atoms in magnetically confined fusion plasmas has been implemented in the ASCOT orbit-following code. The model was verified by comparing simulated reaction mean free paths to analytical values across a range of fusion-relevant parameters. ASCOT was used to simulate beam ions slowing down in the presence of CX reactions in a MAST-U target scenario. ASCOT predicts the CX-induced loss of beam power to be 22%, which agrees to within 15% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In devices with higher temperatures and higher neutral beam injection energies, CX losses are lower due to the strong decrease of the CX cross section as energy increases, and therefore usually neglected. However, in the case of TJ-II NBI plasmas, in particular if they are interesting from the point of view of Alfvén Eigenmodes (AEs) studies (relatively low plasma density), the density of neutrals atoms in the plasma makes the CX losses relevant and they need to be included if a reliable estimate of the fast ion slowing down distribution is desired [15]. In low density conditions, former guiding center calculations done with FAFNER [16] showed that CX losses in TJ-II plasmas can reach up to 30% of the port through power, which represents almost 70% of the available power due to the high level of shine through [17].…”
Section: Introductionmentioning
confidence: 99%
“…In devices with higher temperatures and higher neutral beam injection energies, CX losses are lower due to the strong decrease of the CX cross section as energy increases, and therefore usually neglected. However, in the case of TJ-II NBI plasmas, in particular if they are interesting from the point of view of Alfvén Eigenmodes (AEs) studies (relatively low plasma density), the density of neutrals atoms in the plasma makes the CX losses relevant and they need to be included if a reliable estimate of the fast ion slowing down distribution is desired [15]. In low density conditions, former guiding center calculations done with FAFNER [16] showed that CX losses in TJ-II plasmas can reach up to 30% of the port through power, which represents almost 70% of the available power due to the high level of shine through [17].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of resonant magnetic perturbations and CX on the fast ion behaviour (McClements et al 2018) in MAST (mega ampere spherical tokamak) have been simulated by the guiding-centre and full orbit code OMFC (Tani et al 2016). The TRANSP (Goldston et al 1981) code with its guiding-centre orbit-following module NUBEAM (Pankin et al 2004a,b), has been used to compute CX losses of fast ions in MAST (Tournianski et al 2005) and MAST-U (Ollus et al 2022). The impact of CX on NBI ion losses has been simulated in MAST-U (Ollus et al 2022) by using the ASCOT (Hirvijoki et al 2014) code.…”
Section: Introductionmentioning
confidence: 99%
“…The TRANSP (Goldston et al 1981) code with its guiding-centre orbit-following module NUBEAM (Pankin et al 2004a,b), has been used to compute CX losses of fast ions in MAST (Tournianski et al 2005) and MAST-U (Ollus et al 2022). The impact of CX on NBI ion losses has been simulated in MAST-U (Ollus et al 2022) by using the ASCOT (Hirvijoki et al 2014) code. The NBI ion losses induced by CX has also been simulated in COMPASS (Jaulmes, Westerhof & de Blank 2014) by using the full orbit code EBdyna (Jaulmes et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations